Exponential Global Health Hazards of Pharmaceutical Pollution and Its Preventive Measures: A Comprehensive Review - Renu Tushir; Sanjita Das; Ajesh Chauhan; Saurav Gurjar; Lakshay Bhanwala; Sneha Patnaik; Anushka Jain (Journal of Environmental Health and Sustainable Development)
Introduction: Antimicrobial agents from different categories like antibiotics, anti-parasitic agents, and other agents such as Xeno (estrogens) can exert some intimidating effects on the environment that can be ecotoxicological as well. Disposal of chemicals in the form of drugs in various water bodies such as lakes, ponds, rivers, and commonly used drinking water might cause potential health damage to human, animal, and aquatic life via environmental pollution. Thus, production of such waste requires proper disposal and supervision, which might be a hurdle for the medical personnel, city administrators, workers working in the industry involved in recycling, and planners of policies. Materials and Methods:  The review is taken the help of resources for getting appropriate information are PubMed, Google Scholar, Scopus, Web of Science very carefully. The period of time for article search in databases varied from 2001-2023. The articles between this time range were included. Results: In the present study, an effort was made to pinnacle sources, categories, and information regarding various drugs and regulatory bodies across the globe to control these functions.  To overcome the pharmaceutical pollution issues, functions, categories of wastes, and strategies to resolve were elaborated. Conclusion: The study highlighted the crucial function of pharmacists in reducing pharmaceutical waste and evaluated current water management policies, emphasizing the necessity for cohesive efforts to diminish pollution. Moreover, an examination of existing regulatory frameworks revealed inadequacies and provided suggestions for improved monitoring and enforcement. This comprehensive report aimed to offer practical recommendations for the advancement of sustainable pharmaceutical waste management techniques, aiding in the protection of world health and the environment. Highlights: